Purification and Characterization of Rennin Like Protease from Enterococcus faecium 1.15 Isolated from Indonesia Fermented Bakasam - Putranto, Wendry; Suryaningsih, Lilis; Zaenal, Apon; Mamangkey, Jendri (Publisher Cv. Inara, 2023)
The protease enzyme produced by Lactic Acid Bacteria (LAB) with characteristics similar to rennin is called Rennin Like Protease (RLP). The purpose of the study was to obtain information on the biochemical characteristics of RLP produced by Enterococcus faecium 1.15 as a basis for the utilization of the enzyme. The first stage of the study was observation of the growth curves and the potential of the isolates to produce RLP, biochemical characterization. Rennin Like Protease (RLP) produced by Enterococcus faecium 1.15 which has been purified using Sephadex G-50 has a molecular weight of 42 kDa with biochemical characters, with an optimum temperature of 40 ? and pH of 4.5. The comparison between MCA/PA with a value of 3.74 which is close to the MCA value of Calf Rennet is 1.